Relationship between citizens' readiness and utilisation of digital participation moderated by socio-demographics : A user perspectives in Malaysian local governments - Mohamad Nur Salam, Man (2025)
Public participation is one of the main catalysts in decision-making activities and public policy development within Malaysian government agencies. The integration of digital methods in public participation, also known as digital participation, has been proposed as a means to increase the effectiveness of the public participation process. However, previous studies have highlighted persistent challenges in the implementation and adoption of digital participation, particularly at the local government level in Malaysia. Moreover, many Malaysian citizens remain unaware and lack sufficient exposure to digital participation in local governance. This study aims to identify the level of readiness, the relationship between readiness factors, and the influence of the socio-demographics moderating effect on the readiness factor to utilise digital participation among Malaysian citizens from the context of local government in Malaysia. A tailored research model, based on a modified Unified Theory of Acceptance and Use of Technology (UTAUT), was developed to address the research questions. Using quantitative methods, data was collected through surveys employing convenience sampling. The participants of this study consisted of 484 Malaysian citizens. Data was analysed using IBM SPSS Statistics Version 27 software to calculate mean scores and Pearson’s correlation. SmartPLS 3 software was used to analyse socio-demographics moderation effects through the Partial Least Squares - Structural Equation Modelling (PLS-SEM). The findings revealed mixed readiness levels, ranging from medium to high among participants. Pearson’s correlation analysis confirmed significant relationships between readiness factors and the utilisation of digital participation. However, the socio-demographic moderation effects were found to be statistically insignificant across all tested relationships. This study identifies several key readiness factors that stakeholders in local government agencies in Malaysia can address to promote greater adoption of digital participation, fostering transparency and efficiency in decision-making at the local level. Additionally, the findings contribute valuable insights into current trends in the utilisation of digital participation and provide a foundation for advancing the public participation agenda within Malaysian local governance, making it more inclusive and effective